SELF-INTERNALIZATION FACTORS FOR CONDOM USE AMONG COMMERCIAL SEX WORKERS (CSW) IN PREVENTING HIV / AIDS TRANSMISSION - Rahmawati, Wahyu Diana; M, Listyaning Eko; I, Ribkha Itha; N, Nuril (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The existence of localizations of commercial sex worker (CSW) may increase the HIV/AIDS cases. It might be due to individual?s perception to prevent HIV/AIDS transmission remains low. STI (Sexually Transmitted Infections) such as Gonorrhea and Chlamydia are the diseases which is caused of sexual intercourse. This study aims to describe the internalizations factors to apply condom as the preventive approaches and to investigate the correlation between cognitive level and attuite with condom application. Methodology: This descriptive cross-sectional study was enrolled by 65 of 258 CSW?s clients in Sadar alley, Banyumas Regency, Indonesia. Accidental sampling was used to select the respondents. Inclusion criteria were CSW?s clients, willing to be respondents, and had sexual intercourse in the alley. The dependent variable was condom application and the independent variables were cognitive level and attitude. The data analysis was done by Spearman Rank. Results: More than a half of respondents had a good cognitive level to prevent HIV/AIDS transmission and more than three fourth had a support attitude. Among 65 respondents, 48 of them had intension to use condom. The cognitive level and attitude were found with strong correlation with condom applications (p <0.001). Conclusions: Cognitive level and attitude had an important role related to condom applications. Public health promotor should take an action to educate CSW and CSW?s clients to prevent HIV/AIDS transmission.